Degradation of pretreated agroforestry residues by selected micromycetes - Galić Milica M.; Ćilerdžić Jasmina Lj.; Stajić Mirjana M. (Zbornik Matice Srpske za Prirodne Nauke, 2022)
Nowadays, there are huge amounts of lignocellulosic materials left in agroforestry practice, which can be transformed into useful products. Biomass exploitation could be aiming not only at replacing conventional energy sources but also at preserving biodiversity and natural ecosystems. Five micromycetes were studied with goal to determine their potential to produce active cellulases as well as the ability to decompose pretreated wheat straw and oak sawdust after seven days of solid-state fermentation. Wheat straw was better lignocellulosic substrate than oak sawdust for the production of cellulases in all five micromycetes. Thus, Penicillium solitum BEOFB 1190m has shown to be the best producer of highly active forms of xylanases (7532.36 ± 89.37 U/L). The most active endo- and exocellulases (2299.70 ± 72.17 U/L and 195.66 ± 4.64 U/L, respectively) were produced by Trichoderma harzianum BEOFB 1230m, while the maximal value of β-glucosidase activity (215.69 ± 3.13 U/L) was detected after Fusarium graminearum BEOFB 820m cultivation. T. harzianum also showed high efficiency in wheat straw cellulose and hemicellulose depolymerization (23.90% and 33.00%, respectively), which resulted in the highest dry matter loss (36.25%). The results of the study showed great potential of tested micromycetes to synthesize cellulolytic enzymes and consequently transform abundant, low-cost plant residues such as wheat straw into useful products including biofuel.